Direct comparison of QIAamp DSP Virus Kit and QIAamp Circulating Nucleic Acid Kit regarding cell-free fetal DNA isolation from maternal peripheral blood - Jain, Mark; Balatsky, Alexander Vladimirovich; Revina, Daria Borisovna; Samokhodskaya, Larisa Mikhailovna (Molecular and cellular probes, 2019)
Blood of pregnant women contains cell-free fetal DNA (cffDNA), which is widely used in non-invasive prenatal diagnosis. The modern laboratory equipment market provides huge variety of commercial kits for isolation of circulating nucleic acids, but unfortunately none of them are standardized for isolation of cffDNA, which is a crucial step for success of subsequent analysis. To compare DSPVK and CNAK in terms of cffDNA, cell-free total DNA (cftDNA) yield and resulting cffDNA fraction, as well as to try to explain the possible difference between the efficacy of these kits. Peripheral blood samples were collected from 18 healthy pregnant women (6th-14th week of pregnancy) and from 12 healthy unpregnant subjects. cftDNA was isolated using QIAamp Circulating Nucleic Acid Kit (CNAK) (Qiagen, Germany) and QIAamp DSP Virus Kit (DSPVK) (Qiagen, Germany) from 1 ml of plasma of each sample. Methylation-sensitive restriction was carried out to isolate cffDNA. Yield of cffDNA and cftDNA was quantified using digital PCR. To explain the difference in resulting efficacy of these two kits PCR inhibitors analysis was performed, as well as the optimal plasma input for DSPVK was investigated. Yield of cffDNA using CNAK was statistically significantly higher than using DSPVK (167.62 (125.34–192.47) vs 52.88 (35.48–125.42) GEq/mL, p < 0.001). The same applies to cftDNA yield, CNAK appears to be statistically significantly superior to DSPVK (743.42 (455.02–898.33) vs 371.07 (294.37–509.89) GEq/mL, p < 0.001). cffDNA fraction using CNAK was also higher than using DSVPK (24.75 (14.5–31.53) vs 14.20 (6.88–25.83) %, p = 0.586), although the difference was not statistically significant due to inconsistency of DSPVK results from sample to sample. PCR inhibitors analysis uncovered increased amount of PCR inhibitors in CNAK cftDNA solution, compared to DSPVK (p = 0.002). Usage of 0.5 mL of plasma for cftDNA extraction with DSPVK over 1 mL demonstrates almost 1.8 times higher cftDNA output (p = 0.028), which suggests that this kit is not so viable for volumes of plasma larger than 0.5 mL. We recommend CNAK over DSPVK for quantitative analysis of cffDNA. Nevertheless, DSPVK is definitely suitable for qualitative analysis as well as for research with limited budget, since it is almost 3 times cheaper than CNAK. •Circulating Nucleic Acid Kit is an optimal kit for isolation of cell-free fetal DNA.•DSP Virus kit is suitable for qualitative analysis of cell-free fetal DNA.•Methylation-sensitive restriction helps determine cell-free fetal DNA fraction.•Digital PCR is an accurate method for quantification of cell-free fetal DNA.